Carbohydrate-loading and exercise performance - Hawley, J. A.; Schabort, E. J.; Noakes, T. D.; Dennis, S. C. (Sports Medicine, 1997)
Carbohydrate loading is a popular activity among athletes. However, its effects on varying forms of exercise have not been conclusively established. In this review the authors conclude the following. There is little to no effect of elevating pre-exercise muscle glycogen contents (glycogen supercompensation) above normal resting values on a single exhaustive bout of high-intensity exercise lasting less than 5 minutes. The is little to no effect of elevating pre-exercise glycogen content on moderate-intensity running or cycling lasting 60 to 90 minutes. At the completion of both forms of exercise there are substantial quantities of glycogen still remaining in the working muscles. Elevated pre-exercise muscle glycogen will postpone fatigue by as much as 20% in endurance events lasting more than 90 minutes. In this form of exercise exhaustion usually coincides with critically low levels of glycogen (<25 mM) suggesting that energy from glycogen cannot be replaced by an increased oxidation of blood glucose. Implication. Glycogen loading is not helpful for single bouts of short intense exercise, or moderate intensity endurance activity of up to 90 minutes duration. However, it is helpful for maximum endurance tasks where glycogen levels have the potential to be substantially reduced. It appears that glycogen supercompensation is only valuable for very extended moderate exercise bouts, such as a two-hour training session, or maximum shorter but aerobically-dominant tasks. Glycogen supercompensation may also improve endurance performance when the task is maximal. In this type of activity, performance improvements of 2-3% have been reported.